Use of simulators in post-pandemic dentistry - Gallo-Zapata, Walter (2022)
The pandemic caused by the COVID-19 virus led to the adoption of sanitary measures that affected the normal development of not only work activities but also academic ones. The close down of universities, specifically in dental schools where clinical activity in the last three years of study is essential for the development of procedural and attitudinal competencies, was totally suspended. The aim of this article is to review the post-pandemic use of simulators to make up for the presence of patients. For this purpose, a search of scientific articles was performed in the databases Google Scholar, MEDLINE/PubMed, SCIelo, Scopus, LILACS, during the years 2020-2021. It is necessarily essential for the faculties to adapt their clinical environments to the installation of this technology, as well as training in its use. The review will seek to show the importance of its use in the development of the required competencies. According to the results, it was determined that the use of this technology, basically allows the development of skills, dexterity and confidence in the students without having to put the health and physical integrity of the patient at risk, with the possibility of evaluating and repeating the procedures performed indefinitely.